(untitled) (Journal of Philosophy, Culture and Political Science, 2026)
This article examines the value systems revealed in public discussions of four contemporary Kazakh art activists: Saule Suleimenova, Saule Dyussembina, Vladislav Sludsky and Galiya Toremuratova. The article employs an analytical approach based on Spiral Dynamics theory and conducts a content analysis of 61,263 words from digital publications, interviews, public statements, and other publicly available materials. The study identifies the primary and secondary vMEMEs presented in these narratives. It is studied how these value structures are connected with the socio-political landscape of Kazakhstan. For all significant units of the body, a coding matrix based on the eight-level model «spiral dynamics» was used, which allowed a comparative analysis of different cases. The results show that all four artists operate in complex value systems, with «orange», «green» and «yellow» being the main vMEMEs influencing their communication practices. These levels demonstrate a general orientation towards innovation, civic humanism, systematic reflection and ethical criticism. Secondary memes, especially blue and purple, serve as cultural and moral foundations, while turquoise selectively appears in discussions related to collective healing and universal dignity. Although each artist has a unique value profile, their collective understanding reveals a broader movement towards postmaterialistic and integrative forms of civil expression in Kazakhstan. By focusing on value discourse rather than public perception, the study highlights the capacity of art activism to shape cultural meanings, harmonize collective identities, and express new ethical perspectives in a rapidly changing society. Keywords: art; art-activism; spiral dynamics; visual politics; value systems. Keywords: vMEMEs, art, art-activism, Spiral Dynamics, visual politics, value systems.